Messrs Hawari Hanafi & Co / Ayu Nadia Mohd Radi - Mohd Radi, Ayu Nadia (Faculty of Business and Management, 2023)
Messrs Hawari Hanafi & Co is a law firm that was chosen to make my internship report. Messrs Hawari Hanafi & Co have two branches in Puncak Alam, and Bukit Jelutong, Selangor. The branch I work at is in Bukit Jelutong Selangor. It started from 1st March 2023 until 15th August 2023. In this report, is about company profile, training reflection, SWOT, and also recommendations for SWOT analysis.